2022
DOI: 10.1021/acs.estlett.2c00130
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Ozone Oxidation Chemistry at a Riverine Surface Microlayer as a Source of Nitrogen Organic Compounds

Abstract: Nitrogen (N)-containing organic compounds, including “brown carbon” (BrC), represent an important fraction of organic aerosols. However, little is known about the processes of formation of the secondarily formed N-containing organics in the atmosphere. Here, we investigated the formation of gas-phase organic compounds, including N-containing organics, through interfacial oxidation chemistry of gaseous O3 with an authentic riverine surface microlayer (SML) by using a high-resolution quadrupole Orbitrap mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Most of them are with 3–11 oxygens, similar to organic nitrogen compounds detected in particle phase (Lee et al., 2016). Compounds with one N‐atom are dominant (131) whereas other 40 compounds contain two N‐atoms which is a similar trend with the observed gas‐phase products (Wang et al., 2022) indicating that these N‐containing compounds can likely be released in the gas phase and affect the air quality. Furthermore, 42 homologous series of common N‐containing organic products have been separated by KM and KMD calculation as shown in Figure 6b and listed in Table S4 in Supporting Information .…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Most of them are with 3–11 oxygens, similar to organic nitrogen compounds detected in particle phase (Lee et al., 2016). Compounds with one N‐atom are dominant (131) whereas other 40 compounds contain two N‐atoms which is a similar trend with the observed gas‐phase products (Wang et al., 2022) indicating that these N‐containing compounds can likely be released in the gas phase and affect the air quality. Furthermore, 42 homologous series of common N‐containing organic products have been separated by KM and KMD calculation as shown in Figure 6b and listed in Table S4 in Supporting Information .…”
Section: Resultssupporting
confidence: 74%
“…Figure 1 shows the overview of the condensed‐phase compounds detected before and after ozonolysis of the three SML samples. It has to be noted that one fraction of the observed products in the aqueous phase by FT‐ICR MS were also observed in the gas phase by SESI‐UHR‐MS in our previous study (Wang et al., 2022) indicating the importance of this chemistry for the atmospheric composition. The distributions of the peak intensities prior to ozonolysis were similar among the three observed SML samples.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…With regard to detected m/z 69 by PTR−TOF−MS, the possibility that it could be isoprene was ruled out because it was absent in the mass spectra of TD− GC−MS. Again, with reference to our previous study using U-HR-MS, 25 The chemical composition of SML is a very complex and intriguing issue, but it is known that it contains fatty acids, which are highly reactive with ozone. 2 Indeed, previous studies reported the formation of 3-nonenal (m/z 141, [C 9 H 16 O]H + ) and hexanal (m/z 101, [C 6 H 12 O]H + ) as major products when the monolayer of linoleic acid was oxidized by ozone.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…3 For example, the deposition of ozone (O 3 ) to the sea surface is mainly controlled by the chemical reactivity at the SML. 4−13 Photochemical and photosensitized processes 14−23 and heterogeneous ozone chemistry 24,25 at the SML lead to the production of oxygenated volatile organic compounds (OVOCs) (acids, ketones, aldehydes, etc.). Mungall et al observed OVOCs above sea waters and suggested that they may stem from photosensitized chemistry and heterogeneous reactions of the hydroxyl radical (OH) and O 3 with the organics enriched at the SML.…”
Section: ■ Introductionmentioning
confidence: 99%